ChemInform Abstract: A Regioselective Formal Coupling Reaction Between C(sp2) and C(sp3): o‐Quinodimethane (o‐QDM)‐Mediated Domino Process for the Construction of 3‐(2‐Methylbenzyl)indole Derivatives. Issue 50 (December 2015) - Wang, Miao; Wang, Jungang; Xiang, Jiachen; Wu, Anxin
Abstract: The facile protocol allows the synthesis of the title products from benz[c]oxepins and indoles via a ring‐opening/[1, 5] H‐shift/Michael addition sequence.